This preview shows page 1. Sign up to view the full content.
Unformatted text preview: ε > 0. 2. f (2 n ) = O ( f ( n )) and f ( n 2 ) = ω ( f ( n )). 3. f ( n + 1) = O ( f ( n )) and f (2 n ) = ω ( f ( n )). 4. f ( n + 1) = ω ( f ( n )). 5. f ( n ) 6 = O ( n ), f ( n ) 6 = Ω( n ), and f is strictly monotone increasing. 6. f ( n ) = O ( n ) and f ( n ) 6 = Ω( n ), but f ( n ) 6 = o ( n ). Hint: The ﬁrst four items have simple answers. Only the last two items require some kind of oscillatory behavior of f . 1...
View Full Document
This note was uploaded on 12/13/2011 for the course CSCE 750 taught by Professor Fenner during the Fall '11 term at South Carolina.
- Fall '11